The relative age effect in Poland's elite youth soccer players - Rubajczyk, K.; Rokita, A. (Journal of Human Kinetics, 2018)
The relative age effect (RAE) is related to discrimination against youth athletes born in the last quarter of the calendar year. The current study presents research on the RAE in elite youth soccer players in Poland. Players in the Central Junior League (CLJ) finals represent 0.59% of the 25,756 players under 20 years old (U20). This study analyzed the post-game protocols of the CLJ knockout stage from the 2013/2014 and 2014/2015 seasons as well as the U17-U21 teams during 2015, including only players who played on the field for at least one minute (n = 395). The results revealed the existence of RAE in the examined groups ( CLJ 2013/2014, ?23 = 15.441, p < 0.01, CLJ 2014/2015, ?23 = 20.891, p < 0.001 U17-U21, ?23 = 25.110, p < 0.001). In addition, the results differed by monthly birth distribution in the Polish population (PP) between 1995 and 1999. This study is the first to examine the RAE in youth soccer in Poland. The occurrence of the RAE with regard to the most promising youth and national team players suggests that a similar effect exists among younger age categories. To reduce the RAE related to identifying soccer talent, tools should be implemented to optimize the player-selection process, such as those that consider the biological development of a player. Keywords: talent identification; selection; soccer